The Effect of Patient Weight and Provider Training and Experience on Dosing of Rocuronium. (26th June 2016) - Godwin, N. C.; Rodriguez, L.; Banks, S.; Major, B. T.; Rodriguez, Y.
Abstract : Introduction . Maintenance dosing of neuromuscular blocking agents is complex and varies with patient, procedure, and clinical situation. With this in mind, we sought to identify factors impacting the maintenance dosing of neuromuscular blockers as a step toward identifying best practice with respect to minimizing residual neuromuscular blockade. Methods . Cases utilizing rocuronium from July 1, 2010, to June 30, 2014, at the sponsoring institution were analyzed. Using a mixed model to account for repeated measures, patients were analyzed by dose and weight category as defined by the World Health Organization (eight categories ranging from very severely underweight to very severely obese) as well as by the administering provider's level of experience. Results . The study included 12, 671 patients with a mean age of 49.7 (SD 16.7). Increasing weight category and higher levels of provider experience were associated with higher doses for rocuronium. There were no differences in initial dose or in frequency of maintenance dosing by weight category after controlling for case length. Discussion . The two dosing patterns identified, higher doses for overweight patients and higher doses administered by experienced providers, are modifiable factors that could enhance patient safety.